2011
DOI: 10.1002/jbio.201100037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the diagnostic performance of autofluorescence and diffuse reflectance in oral cancer detection: a clinical study

Abstract: Autofluorescence (AF) and diffuse reflectance (DR) spectroscopic techniques have shown good diagnostic accuracies for noninvasive detection of oral cavity cancer. In the present study, AF and DR spectra recorded in vivo from the same set of sites in 65 patients were analyzed using Principal component analysis (PCA) and linear discriminant analysis (LDA). The effectiveness of these two techniques was assessed by comparison with gold standard and their discrimination efficiency was determined from the area under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…It has been reported that by analyzing the ratio of diffuse reflectance intensity in the oral mucosa at 545 nm and 575 nm, it is possible to distinguish between healthy and cancerous oral lesions due to changes in the spectra at these wavelengths, which are associated with oxygenated hemoglobin in the tissue [34][35][36][37]. While a standard RGB camera is unable to differentiate between these two wavelengths, the IMS allows for a clear distinction.…”
Section: Imaging Of Ex Vivo Oral Tissuementioning
confidence: 99%
“…It has been reported that by analyzing the ratio of diffuse reflectance intensity in the oral mucosa at 545 nm and 575 nm, it is possible to distinguish between healthy and cancerous oral lesions due to changes in the spectra at these wavelengths, which are associated with oxygenated hemoglobin in the tissue [34][35][36][37]. While a standard RGB camera is unable to differentiate between these two wavelengths, the IMS allows for a clear distinction.…”
Section: Imaging Of Ex Vivo Oral Tissuementioning
confidence: 99%
“…Considerable work has been carried out by many groups during the last several years to develop the technique of tissue fluorescence spectroscopy as a suitable method for early diagnosis of oral cancer [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Almost all these studies were done on buccal mucosa, though other sites in the oral cavity, like tongue, lips, and upper and lower palates, also are often found to be sites of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Proper interpretation of the observed fluorescence spectra of these different sites is thus necessary for, not only to develop suitable optical methods for diagnosis, but also to understand the complex biological processes that take place during induction, progression, and regression of oral malignancy, Non-Invasive in vivo Screening of Oral Malignancy Using Laser-Induced Fluorescence Based System and follow up in therapy. In earlier studies on fluorescence spectra of different sites in the oral cavity mostly spectra above 450 nm have only been recorded, and excitation wavelengths have also been limited to 337 nm and above [6,9,16,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations in the relative distribution of NADH and porphyrins in the emission spectra corresponding to 405 nm excitation during the tissue transformation process may be due to (i) in the early weeks of DMBA initiation, the inflammatory response is triggered in the skin, thereby increasing the metabolic activity of the inflammated cells, leading to increased level of NADH in the early tissue transformation conditions namely hyperplasia, papilloma and dysplastic lesions,28 and (ii) during the degree of differentiation increases due to chronic application of DMBA in the mouse skin; the NADH decreases leading to an increased level of porphyrin in the malignant transformation of ESCC and WDSCC lesions 29,30. However, with an increase in the degree of malignancy as in the case of both ESCC and WDSCC lesions, the NADH level decreased in intensity compared with hyperplasia, papilloma and dysplasia lesions.…”
mentioning
confidence: 99%